The potential therapeutic roles of dental pulp stem cells in spinal cord injury - Fu, Jing; Li, Wenjie; Mao, Tengfei; Chen, Zaipeng; Lai, Lili; Lin, Jiachen; Nie, Zhiqiang; Sun, Yunkai; Chen, Yanqin; Zhang, Qin; Li, Xigong (Frontiers in Molecular Biosciences, 2024)
Spinal cord injury (SCI) can lead to serious functional disorders, which have serious impacts on patients and society. The current traditional treatments of SCI are not effective the injured spinal cord is difficult to repair and regenerate. In recent years, stem cell transplantation for the treatment of SCI has been a hot research topic. Dental pulp stem cells have strong abilities of self-renewal and multi-directional differentiation, and have been applied for tissue engineering and regenerative medicine. And dental pulp stem cells have certain advantages in neuro-regenetation, bringing new hope to biotherapy for SCI. This article reviews the characteristics of dental pulp stem cells and their research progress in the treatment of SCI.